2011
DOI: 10.4103/0974-2727.78555
|View full text |Cite
|
Sign up to set email alerts
|

Pancytopenia: A Clinico Hematological Study

Abstract: Background:Pancytopenia is a relatively common hematological entity. It is a striking feature of many serious and life-threatening illnesses, ranging from simple drug-induced bone marrow hypoplasia, megaloblastic anemia to fatal bone marrow aplasias and leukemias. The severity of pancytopenia and the underlying pathology determine the management and prognosis. Thus, identification of the correct cause will help in implementing appropriate therapy.Objectives:To study the clinical presentations in pancytopenia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
67
2
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 4 publications
13
67
2
10
Order By: Relevance
“…12 But recent study by Gayatri et al reported 51.35%. 13 Khunger JM et al demonstrated no neutrophils in megaloblastic anemia. 8 This variation could be due to subjective variation in analysis of peripheral smear.…”
Section: Discussionmentioning
confidence: 99%
“…12 But recent study by Gayatri et al reported 51.35%. 13 Khunger JM et al demonstrated no neutrophils in megaloblastic anemia. 8 This variation could be due to subjective variation in analysis of peripheral smear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tilak et al [6]in their study conducted in 1999 found that the most common cause of pancytopenia was megaloblastic anaemia (68%) with aplastic anaemia being second most common cause (7.7%). Megaloblastic anaemia was found to be main cause of pancytopenia in the studies of Gayatri et al [12] , Deepak kumar et al [13] in 74%…”
Section: Discussionmentioning
confidence: 99%
“…The highest incidence by age, 33 (0.15%) cases, is seen in the age group of 40-60 years, which is slightly higher than incidence (29.4%) for the age group of 15-30 years in the studied conducted by Pathak et al [10] ( Table 2) and15-35 years with an incidence of 43% in studies conducted by Sweta et al [11] . The highest incidence (29.04%) by age according to a study by Gayatri and Rao et a [12] is noted in the age group of 2-18 years. The highest age incidence of pancytopenia in the current study is nearly similar to the findings of Deepak Kumar et al [13] which is 30-49 years.…”
Section: Discussionmentioning
confidence: 99%
“…Megaloblastic anemia was the most common cause of pancytopenia (48.9%) in our study which is comparable to other studies. [4,6,7] The high prevalence of nutritional anemia in India has been cited for the increased frequency of megaloblastic anemia.Vitamin B12 deficiency was more common than folate deficiency in our study. Among the nutritional anemias, vitamin B 12 deficiency is more prevalent than folate deficiency as reported by authors in their study from Pakistan.…”
Section: Common Causes Of Pancytopenia Compared To Other Studiesmentioning
confidence: 99%
“…[8] Incidence of hypoplastic anemia/ aplastic anemia varies from 7% to 30% among pancytopenia patients [3,4,5,6,7 ] . In our study it was 15.2% which was comparable to Khodke K et al [6] and Khunger JM et al [1] .…”
Section: Common Causes Of Pancytopenia Compared To Other Studiesmentioning
confidence: 99%